Polycystic ovarian syndrome (PCOS) awareness among young women of central India - Patel, Jaya; Rai, Shailesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Polycystic ovarian syndrome (PCOS) associated with multiple presentation in females although it is common disorder but due to lack of knowledge females often delays in getting confirm diagnosis and treatment. PCOS remains a syndrome and as such no single diagnostic criterion is sufficient for clinical diagnosis. Objective: To assess the knowledge about PCOS in young women. Methods: Cross sectional study was performed on 400 women of age group 18-30 years either studying in Colleges or working in Indore city. Written informed consent was obtained and simple random technique was applied for selection of study participants. Pre-designed, pre-tested, semi-structured questionnaire was used for data collection. The data collected were analyzed through percentages and frequencies using Excel. Relevant statistical test was applied was applied and p value was calculated where ever required and considered statistically significant when it is <0.05. Results: Among 400 participants, only 41% of the women were aware of the term PCOS. 46% of the subjects who were aware about the organ system involved in this disease. Most of the people know about this disorder through friends or relatives. 49% of the women knew about the various signs and symptoms associated with PCOS. Conclusions: The results of present study show that very few of the young women understand what this disease is and what are the earliest symptoms that should alarm them to consult a physician. Discussion with the girls in college authors came to know that most of the people are considering menstrual pain and irregularities as a part of their physiological process and do not consider consulting a doctor.